Reducing relative food reinforcement in infants by an enriched music experience. Issue 4 (April 2016) - Kong, Kai Ling; Eiden, Rina D.; Feda, Denise M.; Stier, Corrin L.; Fletcher, Kelly D.; Woodworth, Elizabeth M.; Paluch, Rocco A.; Epstein, Leonard H.
Abstract : Objective: The reinforcing value of food may be established early in life. Research shows that infant weight status is related to the relative reinforcing value of food versus non‐food alternatives (food reinforcing ratio, FRR). The purpose of this pilot study was to assess the effects of a 6‐week music enhancement program (Music Together®, n  = 14) versus an active play date control group ( n  = 13) on the FRR in 9‐ to 16‐month‐old infants who were high in relative food reinforcement. Methods: Participating parents and infants attended six weekly 45‐min group classes. Parents in the music group and the play date group were encouraged to listen to the Music Together program CD or play with the play date group's toy with their infants at home, respectively. Results: Intent‐to‐treat analysis showed a decrease in FRR for infants in the music group (mean ± SD: −0.13 ± 0.13) in comparison to a slight increase in the control group (0.04 ± 0.11) ( F [1, 24]  = 11.86, P  = 0.002). Conclusions: These findings provide evidence that relative reinforcing value of food can be reduced by promoting alternative reinforcers at an early age.